Comparisons of optical characteristics of two upward lightning flashes triggered by a nearby positive cloud-to-ground lightning. (February 2020) - Wang, X.; Zhao, X.; Cai, H.; Liu, G.; Liao, M.; Qu, L.; Hu, S.
Abstract: The propagation characteristics of two upward negative lightning flashes, which were initiated from the tops of two tall grounded structures immediately after the return stroke (RS) initiation of one nearby positive cloud-to-ground (CG) lightning flash, have been investigated and compared based on high-speed video observations. Two upward flashes show significant difference in their propagation characteristics mainly due to the existence of lower cloud layer near the Canton tower. Upward flash initiated from the top of Canton tower produces several large luminous pulses, with the enhanced luminosity mostly concentrating near the lower cloud, and it propagates faster beyond the lower cloud, while the brightness of the other upward flash does not vary much and distributes almost uniformly along the discharge channel. The major reason for these differences might lie in the instantaneous negative charge neutralization inside the lower cloud with the positive charges along the discharge channel, when the positive leader propagates upward across the lower cloud layer. After about 90 ms the upward flash initiated from the tall building produces a dart-leader subsequent RS, but it extinguishes faster than the other one. Highlights: Two upward flashes were immediately triggered by a nearby positive CG lightning. Two upward negative flashes have obviously different propagation characteristics. Lower cloud near Canton tower has a great influence on the behavior of upward flash.